2020
DOI: 10.1371/journal.pcbi.1008286
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the circularity in circular analyses: Simulations and formal treatment of the flattened average approach

Abstract: There has been considerable debate and concern as to whether there is a replication crisis in the scientific literature. A likely cause of poor replication is the multiple comparisons problem. An important way in which this problem can manifest in the M/EEG context is through post hoc tailoring of analysis windows (a.k.a. regions-of-interest, ROIs) to landmarks in the collected data. Post hoc tailoring of ROIs is used because it allows researchers to adapt to inter-experiment variability and discover novel dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…The key step in this procedure is the merging of probe and irrelevant. Essentially, as verified in simulation and proof (Bowman et al., 2020), this merging means that, under the null, selecting this window of interest from the resulting aggregated ERP is mathematically orthogonal to the probe minus irrelevant contrast. Accordingly, under the null, there is no increased probability of the probe being different from irrelevant at the window selected on the aggregated ERP.…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…The key step in this procedure is the merging of probe and irrelevant. Essentially, as verified in simulation and proof (Bowman et al., 2020), this merging means that, under the null, selecting this window of interest from the resulting aggregated ERP is mathematically orthogonal to the probe minus irrelevant contrast. Accordingly, under the null, there is no increased probability of the probe being different from irrelevant at the window selected on the aggregated ERP.…”
Section: Methodsmentioning
confidence: 84%
“…Statistical analysis was conducted according to the Aggregated Grand Average of Trials (AGAT) method (Bowman et al., 2020; Brooks et al., 2017). For this, the trials for the probe and irrelevant conditions were merged to provide one aggregated ERP per participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERPs are typically characterised by a series of positive and negative excursions from baseline, which correspond to the stimulus evoked onset transients, before the time‐series settles back, and we wanted to capture only this period. To do this, we focussed on the aggregated average (Bowman et al, 2020; Brooks et al, 2017) across the three stimulus conditions (for Onsets 2–8). ROIs can be identified on the aggregated average, without inflating false‐positive rates, since it does not reflect condition (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…ROIs can be identified on the aggregated average, without inflating false‐positive rates, since it does not reflect condition (i.e. stimulus) differences, which for us amounts to the PGI (Bowman et al, 2020; Brooks et al, 2017). However, an initial inspection of our data revealed that the aggregated average did not settle back to baseline but rather fell to a constant, positive DC level.…”
Section: Methodsmentioning
confidence: 99%